Abdominal Decompression in Children. (22nd March 2012) - Ejike, J. Chiaka; Mathur, Mudit
Abstract : Abdominal compartment syndrome (ACS) increases the risk for mortality in critically ill children. It occurs in association with a wide variety of medical and surgical diagnoses. Management of ACS involves recognizing the development of intra-abdominal hypertension (IAH) by intra-abdominal pressure (IAP) monitoring, treating the underlying cause, and preventing progression to ACS by lowering IAP. When ACS is already present, supporting dysfunctional organs and decreasing IAP to prevent new organ involvement become an additional focus of therapy. Medical management strategies to achieve these goals should be employed but when medical management fails, timely abdominal decompression is essential to reduce the risk of mortality. A literature review was performed to understand the role and outcomes of abdominal decompression among children with ACS. Abdominal decompression appears to have a positive effect on patient survival. However, prospective randomized studies are needed to fully understand the indications and impact of these therapies on survival in children.